Managing disaster preparedness and response for hybrid collections in Australian national and state libraries. Issue 4 (2nd October 2018) - Brown, Heather
ABSTRACT: In the 21st century cultural heritage collections are increasingly hybrid; not only do they contain physical materials, they also contain growing collections of digital materials. However, typically their disaster plans focus on managing just the physical collections. The digital collections are managed separately; commonly the disaster planning role is assigned to IT systems staff. This research investigated disaster preparedness in Australian national, state and territory libraries to gauge what areas might be common in disaster management of physical and digital collections, and also what might be different. It further investigated the potential for developing an integrated disaster plan that could align disaster responses across all collection formats – physical and digital. The author worked with experienced State Library of Queensland (SLQ) staff to develop a 'proof of concept' template for an integrated disaster plan, using the SLQ plan as a model. The research confirmed the feasibility and the benefits of an integrated plan as a 'one stop shop' source of disaster information. The research outcomes potentially have implications for more effectively protecting hybrid collections across the cultural heritage sectors internationally. Abbreviation : Information Technology (IT)